Effectiveness of Propofol versus Dexamethasone for Prevention of Postoperative Nausea and Vomiting in Ear, Nose, and Throat Surgery in Tikur Anbessa Specialized Hospital and Yekatit 12th Hospital, Addis Ababa, Ethiopia - Abere Tilahun Bantie; Wosenyeleh Admasu; Sintayehu Mulugeta; Abera Regassa Bacha; Desalegn Getnet Demsie (Anesthesiology Research and Practice)
Background. Postoperative nausea and vomiting (PONV) remain as common and unpleasant and highly distressful experience following ear, nose, and throat surgery. During ENT surgery, the incidence of PONV could be significantly reduced in patients who receive dexamethasone and propofol as prophylaxis. However, the comparative effectiveness of the two drugs has not been assessed. The aim of this study was to compare the effectiveness of propofol and dexamethasone for prevention of PONV in ear, nose, and throat surgery. Methods. This study was conducted in 80 patients, with ASA I and II, aged 18–65 years, and scheduled for ENT surgery between December 20, 2017, and March 20, 2018. Patients were randomly assigned to Group A and Group B. Immediately after the procedure, Group A patients received single dose of intravenous (IV) dexamethasone (10 mg/kg) and Group B patients were given propofol (0.5 mg/kg, IV), and equal follow-up was employed. The incidence of PONV was noted at 6th, 12th, and 24th hour of drug administration. Independent t-test and Mann–Whitney test were used for comparison of symmetric numerical and asymmetric data between groups, respectively. Categorical data were analyzed with the chi-square test, and p value of < 0.05 was considered as level of significance. Results. The incidences of PONV throughout the 24-hour postoperative period were 35% in the propofol group and 25% in the dexamethasone group. Statistical significance was found in incidence of PONV (0% versus 22.5%) and use of antiemetic (0% versus 5%) between dexamethasone and propofol groups, respectively, at 12–24 hours. Over 24 hours, 5% in dexamethasone group and 12.5% in propofol group developed moderate PONV, while none of the participants felt severe PONV. Conclusions. Dexamethasone was more effective than propofol to prevent PONV with lower requirements of rescue antiemetics.